Iran’s membership in the Shanghai Cooperation Organization (SCO) Economic, Trade and Political Affairs - Nabipour, Pourya (National Interest, 2021)
This paper aims to provide a better understanding of the Iranian accession into the Shanghai Cooperation Organisation (SCO) and to answer the important question of whether one can identify substantial payoffs from “deep integration” (combining economic and political aspects of Iran’s SCO membership). Iran’s pursuit of full membership in the Shanghai Cooperation Organisation (SCO) seems to be reinforced by the distrust towards the global West, and its genuine Look East Policy with the prospect of allying with Russia and China. Indeed, the SCO is perceived as a geopolitical counterweight to the United States. Because of the distrust, Iran failed to get included in regional or international security architecture and the West did not embrace a new Iran wholeheartedly. This logic was grounded in a political climate of distrust, asymmetries of power and unilateral ethnocentrism which were hampering any initiative for trust-building and de-escalation. Tehran began to look for a place in the international system by relying on domestic discourses and ideas emanating from within the domestic ideas about Iran’s identity and consequently approaching superpowers of the global East. Crippling sanctions, threats of military intervention, cyber warfare, regime change and regime destabilization efforts were from Iran’s perspective the policies that were genuinely used against Iran and therefore contentious. By joining the SCO Iran can downplay the effect of sanctions.